Security and Defence Issues, New Zealand, 1982 (ADA Dataverse, 2018)
Topics in this survey include: ANZUS treaty; forms of New Zealand cooperation with the U.S. under ANZUS; relative benefits of ANZUS to U.S. and New Zealand; U.S. protection of New Zealand national security; maintenance of ANZUS alliance between U.S. and New Zealand; military strength of U.S. versus Russia; most powerful nation in the Asian-Pacific region; security in the Asian-Pacific region; visit by U.S. nuclear-powered warships to New Zealand ports; self-placement on left-right spectrum. Standard variables include household size, age, marital status, schooling, occupation of respondent or of main income earner, household income, sex, area. This study is the first of four (SSDA No's 521 to 524) commissioned by the United States Information Service between 1982 and 1985 on New Zealanders' attitudes to defence issues. Similar studies were carried out in Australia at the same time (SSDA No's 525 to 532) which contain some parallel questions.